The Loom of Life: Traditional Handloom Weaving as a Means of Livelihood and Cultural Continuity - PEREZ, FEDELYN (Azal Arts and Humanities, 2026)
This qualitative study explores the dual role of traditional handloom weaving as a vital source of livelihood and a vessel for cultural preservation among the artisans of Barangay Gomez, Cabarroguis, Quirino. In an era of rapid globalization and mechanized textile production, the handloom industry representing approximately 3.5 million workers globally nfaces significant threats to its sustainability. Using a phenomenological approach, this research delves into the lived experiences of traditional weavers to understand how this craft supports their families and reinforces their ethnic identity. The study identifies the challenges and struggles encountered by these artisans, including intense competition from factory-made fabrics, limited resource access, and the risk of disappearing indigenous knowledge. Through in-depth interviews and thematic analysis, the research documents the coping mechanisms and strategies employed by weavers and stakeholders to navigate these contemporary obstacles. A key focus is placed on the intergenerational and informal learning processes, such as family apprenticeships, which serve as critical pedagogical tools for passing down cultural values and manual skills. The study portrays traditional handloom weaving in Barangay Gomez as a complex intersection of economic survival and cultural resilience. Identified as a "secondary safety net," the craft provides vital cash flow for rural families to meet immediate needs like education and food when primary income from farming is delayed. Beyond its financial role, weaving serves as a critical vessel for ethnic identity, where the transmission of indigenous knowledge through family apprenticeships acts as a "first classroom" to preserve tribal history and heritage. However, this tradition faces existential threats from the rise of mechanized fabrics, a lack of operational capital, and a widening intergenerational gap characterized by declining interest among the youth. Despite these challenges, the artisans maintain a sense of "engaged patience," leveraging community associations and government support to transform their manual labor into a tool for both household stability and cultural continuity. Keywords: cultural preservation, phenomenological, qualitative research, traditional handloom weaving